Biodegradation of organophosphorus insecticide chlorpyrifos into a major fuel additive 2,4-bis(1,1 dimethylethyl) phenol using white-rot fungal strain Trametes hirsuta MTCC-1171 - Patil P.D.; Singh A.A.; Yadav G.D. (My University, 2025)
Biodegradation of chlorpyrifos, a widely used organophosphorus insecticide, was accomplished by using a white-rot fungal strain (Trametes hirsuta MTCC-1171). The experimental results showed that the fungal strain can effectively and rapidly degrade chlorpyrifos while using it as a sole source of carbon and energy when provided with mineral salt medium (MSM). The optimum experimental conditions for degradation of chlorpyrifos in liquid media can be summed as follows: initial pH 6.0; mycelial inoculum 0.18 ​± ​0.01 ​g ​L−1 (dry weight); chlorpyrifos concentration 150 ​mg ​L−1; pH 6.0; temperature 30 ​°C; and shaking speed 150 ​rpm. Under these optimal experimental parameters, T. hirsuta MTCC-1171 achieved ≥95% degradation of chlorpyrifos in 16 ​h of incubation. The degradation rate was quantified by employing HPLC followed by identification of degradation metabolites using gas chromatography–mass spectrometry (GC-MS). 2,4-Bis (1,1 dimethylethyl) phenol, a fuel additive, was found to be a major metabolite product of chlorpyrifos degradation. However, no metabolite bioaccumulation was observed in the process. Additionally, soil studies were carried out to investigate the degradation ability of the strain against chlorpyrifos, in a natural environment. During the assessment 37 ​± ​2.3% degradation was observed after 15 days of incubation. These results illustrate that T. hirsuta MTCC-1171 has a potential of using chlorpyrifos as a sole source of carbon. Besides, fundamental understanding gained through this work lays a foundation to investigate efficient and rapid bioremediation processes in agricultural and forest environments. © 2021 Indian Chemical Society